Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/1750-3841.12496
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Muscle Exudate Protein Composition as an Indicator of Beef Tenderness

Abstract: This research showed that the protein profiles of exudates that accumulate on the surface and in the packaging of beef change with meat aging and tenderness. These data suggest that muscle exudates may be a good source of protein markers that are useful in the development of rapid, noninvasive methodologies for predicting beef tenderness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Compared to the data presented in the work of Greaser (), a similar amount was observed for PFK, CK/PGAK, and PGAM. Similar values were also observed for PGM, CK/PGAK, and PGAM in the study of Bowker and others (), while not very large differences were found for EN, PHb/PHbK in comparison to data shown in Table . These differences could be explained by the results of Marino and others (), who stated that changes or differences in sarcoplasmic protein profile depend on changes that occurred during aging or breed differences.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Compared to the data presented in the work of Greaser (), a similar amount was observed for PFK, CK/PGAK, and PGAM. Similar values were also observed for PGM, CK/PGAK, and PGAM in the study of Bowker and others (), while not very large differences were found for EN, PHb/PHbK in comparison to data shown in Table . These differences could be explained by the results of Marino and others (), who stated that changes or differences in sarcoplasmic protein profile depend on changes that occurred during aging or breed differences.…”
Section: Discussionsupporting
confidence: 88%
“…As these authors stated, different mechanisms could be responsible for the changes such as isoelectric precipitation due to the pH decline or post mortem degradation. Ouali and others (), Bowker and others (), Sierra and others (), Di Luca and others (), and Canto and others () showed that these proteins could be biological markers for tenderness, color stability, and WHC prediction.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, a significantly higher content of PGM was measured in drip loss from meat of lambs fed with SeY (Table 3). Many studies have shown that sarcoplasmic proteins appeared as indicators of meat ageing and as biomarkers of some quality attributes, tenderness in particular (Di Luca et al, 2011;Sierra et al, 2012;Ouali et al, 2013;Bowker et al, 2014;Marino et al, 2014;Picard et al, 2015). These proteins include GAPDH, a, b, c -means with different superscripts in the same row differ significantly at P α ≤ 0.05.…”
Section: Effect Of Lamb Diets On Drip Loss Protein Profilementioning
confidence: 99%